2009
DOI: 10.1242/jcs.046870
|View full text |Cite
|
Sign up to set email alerts
|

A FAK-p120RasGAP-p190RhoGAP complex regulates polarity in migrating cells

Abstract: Directional motility is a complex process requiring the spatiotemporal integration of signals that regulate cytoskeletal changes, and the establishment of an anteroposterior or polarized cell axis. Focal adhesion kinase (FAK) promotes cell migration, but a molecular role for FAK in promoting cell polarity remains undefined. Here, using wound healing and Golgi-reorientation analyses, we show that fibroblast, endothelial and carcinoma polarity during cell migration requires FAK and is associated with a complex b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
133
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(139 citation statements)
references
References 56 publications
6
133
0
Order By: Relevance
“…This suggests that although CLEC14A is localized at cellto-cell contacts, it may be poised to have a sensing role at the leading edge. It is well established that the Golgi apparatus orientates toward the direction of cell movement (Tomar et al, 2009). Staining of the Golgi with the marker GM130 showed that CLEC14A polarizes to the HUVEC leading edge (Figure 4c), providing further evidence for a role for this protein in environmental sensing and cell migration.…”
Section: Cellular Localization Of Clec14a In Endothelial Cellsmentioning
confidence: 67%
“…This suggests that although CLEC14A is localized at cellto-cell contacts, it may be poised to have a sensing role at the leading edge. It is well established that the Golgi apparatus orientates toward the direction of cell movement (Tomar et al, 2009). Staining of the Golgi with the marker GM130 showed that CLEC14A polarizes to the HUVEC leading edge (Figure 4c), providing further evidence for a role for this protein in environmental sensing and cell migration.…”
Section: Cellular Localization Of Clec14a In Endothelial Cellsmentioning
confidence: 67%
“…DLC1 is thought to serve as a tumor suppressor protein by antagonizing the oncogenic activity of Rho proteins in liver cancer (Wong et al, 2005;Xue et al, 2008). In contrast, p190A RhoGAP-deficient fibroblasts showed a defect in polarized cell migration (Tomar et al, 2009) although they did not exhibit any obvious defects in adhesion on extracellular matrix (Jiang et al, 2008). In both cases, the GAP activity of DLC1 and p190A was implicated in the regulation of cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a critical role for FAK as a regulator of adhesion dynamics (4 -7). In addition, FAK has been shown to mediate the tyrosine phosphorylation of p190RhoGAP as a negative regulator of Rho activity in focal adhesion turnover and polarity (5,8). Furthermore, microtubule-induced focal adhesion disassembly requires FAK and dynamin (9).…”
mentioning
confidence: 99%